Knowledge, Perception, and Willingness to Use Telepharmacy Among the General Population in Indonesia - Nesqi N. Tjiptoatmadja; Sofa D. Alfian; Sofa D. Alfian (Frontiers Media S.A., 2022)
IntroductionCOVID-19 emerged as a pandemic in early 2020. Various steps were taken in an attempt to decrease the spread, which resulted in limited mobility. As people were dissuaded from going out, multiple numbers of digitalized pharmacy services arose to fulfill people's needs for medicine. The objective of this study was to assess knowledge, perception, and willingness to use telepharmacy services and the affecting factors among the general population in Indonesia.Patients and MethodsA cross-sectional study was conducted with the inclusion criteria of Indonesian citizenship, living in Indonesia, and agreement to participate. Details of demographic characteristics, knowledge and perception of telepharmacy services and willingness to use them were collected using an online questionnaire that was adapted from a previous study. The results were analyzed using a descriptive analysis method. The associations between demographic characteristics and knowledge, perception, and willingness to use telepharmacy services were tested with the Mann-Whitney U Test.ResultsOf 203 participants participated in this study, 51% of them had heard about telepharmacy. Over 98% of the participants had a positive perception of telepharmacy services. The majority of those who had never used it were willing to try telepharmacy services in the future. Age and educational level were significantly associated with knowledge of telepharmacy services. No associations were observed between demographic characteristics and perception and willingness to use telepharmacy services.ConclusionsGeneral population in Indonesia had a fair knowledge, a positive perception, and were willing to use telepharmacy services. Interventions to increase knowledge of telepharmacy in Indonesia need to target older adults and people who are less educated.